Severe Peripheral Arterial Compromise in Polyarteritis Nodosa: A Case of Acute Limb Ischemia: Compromiso arterial periférico severo en la poliarteritis nudosa: un caso de isquemia aguda de la extremidad - Anggraeni, Mayang; Awalia, Awalia (Gaceta Médica de Caracas, 2025)
Polyarteritis nodosa (PAN) is a rare vasculitis of medium-sized arteries that can occasionally present as acute limb ischemia (ALI). We report a case of a 31-year-old male with right foot ALI. Imaging revealed arterial occlusion, and the patient met four of the 1990 American College of Rheumatology (ACR) criteria for PAN. Initial therapy with azathioprine and low-dose glucocorticoids was ineffective, but clinical improvement occurred after switching to mycophenolate sodium and increasing steroid dosage. This case emphasizes the importance of considering PAN in ALI and highlights the role of early diagnosis and immunosuppressive treatment to prevent limb loss.